Changing identities in the narratives of academic writing - Rantala-Lehtola, Kati (Journal of Academic Language and Learning, 2025)
Even though identity formation is seen as essential in learning academic writing, it has not received much attention at the Bachelor thesis level in higher education research. This narrative case study focuses on the identity formation of two young students of philosophy during their bachelor's thesis writing processes by applying narrative analysis and the model of the hero’s journey to interview data. The study demonstrates students’ adaptation and resistance to institutional norms and social practices and identifies many possible identities, including an institutional one and two different heroes: the grower and the fighter. The findings suggest that students recognise that the institutional narrative of bachelor’s thesis writing has a clear impact on their identity transformations. This study challenges the idea of purely rational and technical understandings of academic writing and describes it as a diverse transformational journey which can be utilised in revealing underlying questions about academic practices and assumptions in order to help students understand academic writing and their actions more deeply. The study offers cultural archetypes as a pedagogical way to explore students’ learning experiences and identity change in becoming an academic writer. Additionally, useful guiding questions are provided for pedagogical use.